Bone Marrow Burkitt Lymphoma in a Child - Matija Knežić; Irena Seili Bekafigo; Jelena Roganović; Ita Hadžisejdić; Nives Jonjić (Hindawi Limited, 2020)
Burkitt lymphoma (BL) is a highly aggressive but potentially curable disease as long as adequately treated within due time. BL may occur primarily and exclusively in the bone marrow as a form of peripheral and extranodal disease. BL cases with isolated bone marrow involvement are challenging in regard to a prompt diagnostic process. We report a case of a sporadic extranodal subtype of isolated bone marrow BL in an 11-year-old boy. Bone marrow aspiration and biopsy, flow cytometry, and immunohistochemistry along with cytogenetics are compulsory in order to achieve the adequate diagnosis.